2018
DOI: 10.1210/jc.2018-01307
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Adrenal Insufficiency in X-Linked Adrenoleukodystrophy: An International Collaboration

Abstract: Context Primary adrenal insufficiency is an important clinical manifestation of X-linked adrenoleukodystrophy (ALD). Other manifestations include spinal cord disease and/or inflammatory demyelinating cerebral disease. Implementation of newborn screening requires natural history data to develop follow-up recommendations. Objective To delineate the natural history of adrenal insufficiency in male patients with ALD and to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
128
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 28 publications
3
128
0
4
Order By: Relevance
“…The lifetime incidence of adrenal disease in ALD males is about 80% with 46.7% developing adrenal hormone deficiency in childhood, 6 months–10 years of age, 28.6% ages 10–40 years and only 5.6% after the age of 40 years (Huffnagel, Laheji, et al, ). The fetal adrenal in ALD males has the abnormal pathology and biochemistry found in adrenals of postnatal males with ALD.…”
Section: Cell‐ and Tissue‐specific Pathologymentioning
confidence: 99%
See 3 more Smart Citations
“…The lifetime incidence of adrenal disease in ALD males is about 80% with 46.7% developing adrenal hormone deficiency in childhood, 6 months–10 years of age, 28.6% ages 10–40 years and only 5.6% after the age of 40 years (Huffnagel, Laheji, et al, ). The fetal adrenal in ALD males has the abnormal pathology and biochemistry found in adrenals of postnatal males with ALD.…”
Section: Cell‐ and Tissue‐specific Pathologymentioning
confidence: 99%
“…The site of adrenal dysfunction is in good agreement with the fact that ABCD1 protein is found in the adrenal cortex but not in the adrenal medulla, while ABCD2 shows the opposite distribution (Troffer‐Charlier et al, ). The VLCFA in the cell membranes may also interfere with ACTH and gonadotropin binding to their receptors (Burtman & Regelmann, ; Huffnagel, Laheji, et al, ). Similar biochemical changes and pathology are found in the Leydig cells of the testes leading to defective hormonogenesis.…”
Section: Cell‐ and Tissue‐specific Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective study by Huffnagel et al found that the first manifestation of X‐ALD was adrenal insufficiency in 37.7% of cases, followed by spinal cord disease (25.2%) and cerebral disease (14.5%). While almost all male patients with X‐ALD will develop adrenal insufficiency during their life and 80% are diagnosed before adulthood, the disease may remain clinically silent for some time .…”
Section: Introductionmentioning
confidence: 99%